AB0971 New Availability of an Old Modality; Useful Grading System for Gout Tophi on Plain Radiography. (10th June 2014) - Kim, H.-O.; Suh, Y.S.; Kim, J.-M.; Kim, S.-H.; Cheon, Y.-H.; Lee, W.-S.; Yoo, W.-H.
Abstract : Background: Gout is caused by hyperuricemia related to altered purine metabolism characterized by monosodium urate (MSU) crystals deposition into the joints, particularly the first metartarsophalangeal joint (1st MTPJ). Chronic gout is characterized by the presence of tophi, chronic granulomatous synovitis and bone erosion. As well known, bone erosion is a strong predictor of musculoskeletal disability and is strongly associated with the presence of gout tophi. The size of gout tophi can be decreased when serum urate level is maintained below 6mg/dl. Therefore tophi measurement may reflect outcome after urate-lowering therapy in chronic gout. Plain radiography remains the most widely used imaging modality in the clinical practice. In our knowledge, however, there have been no grading system for tophi on plain radiography. Objectives: The aim of our study is to investigate the usefulness of new grading system for gout tophi by plain radiography. Methods: 334 patients who fulfilled ACR diagnostic criteria of gout and had anteroposterior plain radiography of both 1st MTPJs included retrospectively in our study. Two rheumatologist evaluated gout tophi, soft tissue swelling, bone erosion (BE) and joint space narrowing (JSN) on plain radiography, independently. The agreement between two observer were good (k>0.08). Gout tophi were defined as increased densities which are distinct from adjacent soft tissues. They were graded by measuring maximum diameters vertically and horizontally, and scored by adding up the scores of grades. The vertical diameter of tophi was measured at both sides of proximal phalanges (PPs). The horizontal diameter was measured at lateral side of PP. The measurement of maximum vertical diameter of tophi were graded as follows: grade 0, no tophi; grade 1, the presence of tophi is suspicious; grade 2, less than half of maximum vertical diameter of PP; grade 3, half or more of and less than the maximum vertical diameter of PP; grade 4, more than the maximum vertical diameter of PP. The maximum horizontal diameter of tophi was measured including the adjacent swollen soft tissues, and graded as follows: grade 0, no tophi; grade 1, less than half of maximum horizontal diameter of PP; grade 2, half or more of and less than the maximum horizontal diameter of PP; grade 3, more than the maximum horizontal diameter of PP (Figure 1 ). Results: 111 (33.3%) of 334 patients had abnormal findings (gout tophi; 26.9%, BE; 22.2% and JSN; 7.8%) at initial plain radiography. 43 patients showed tophi and/or soft tissue swelling on plain radiographs. 31 of 43 patients showed improvement of tophi on follow-up plain radiographs. 23 of 31 patients had less than 6 mg/dL of serum urate level after treatment. Points by new grading methods differed significantly between the patient group having 6 mg/dL or more and the patient group having less than 6 mg/dL of serum urate level after hypouricemic treatment ( p =0.05). Conclusions: New grading system for gout tophi on plain radiography is useful for evaluating changes of gout tophi after hypouricemic therapy. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4164